Kidnapped - Escott, John.; Cuzik, David; Stevenson, Robert Louis, 1850-1894. (Harlow: Pearson Education, 2008)
After his parents die, young David Balfour goes to the house of his uncle Ebenezer. But his uncle is a dangerous man. When he puts David on a ship to America, a difficult and dangerous time begins. But who is the stranger on the ship? Can he help David?
1 2
Keywords: Readers; Kidnapping victims -- Juvenile fiction; Teenage boys -- Juvenile fiction; Disinheritance -- Fiction; Scotland -- History -- 18th century -- Juvenile fiction